Penyediaan Jasa Layanan Supervisi Pembangunan Rumah Tinggal di Kota Surabaya sebagai Implementasi Kesiapan Berwirausaha oleh Tim Pengawas Siswa SMK Negeri 2 Surabaya - Ernida Nur Islami (Universitas Islam Balitar Blitar, 2025)
The entrepreneurial product that the author will discuss in this article is the provision of residential construction supervision services in the city of Surabaya by the student supervisory team at SMK Negeri 2 Surabaya. The supervision service business is considered capable of being implemented because students at SMK Negeri 2 Surabaya already have the competency to become supervisors. The aim of this service provision business is because SMK Negeri 2 Surabaya has qualified resources so that it can be used as a profitable business opportunity. The methods used in implementing the coconut chips entrepreneurship program include preparation, market research and product formulation, and marketing strategies